Food Security Transformation: Impact Analysis of IoT-Based Irrigation Water Consumption Patterns in Climate Change Adaptation in Modern Agricultural Systems - Fikri Putra (CV. HEI PUBLISHING INDONESIA, 2024)
The transformation of modern agricultural systems through the application of Internet of Things (IoT) technology is a strategic solution in facing the challenges of food security due to climate change. This study aims to analyze the impact of IoT-based irrigation water consumption patterns on water use efficiency, crop productivity, and soil quality in tropical agricultural land. The study was conducted by designing an automatic irrigation system based on ESP32 and soil moisture sensors, and testing its effectiveness during one planting season on 1.5 hectares of land. The results showed that the IoT irrigation system was able to reduce water consumption by up to 35% compared to conventional methods, maintain soil moisture within the optimal range, and increase crop yields by 12%. Furthermore, despite ongoing difficulties with technical assistance and initial investment expenditures, the quality of soil nutrients is better maintained, and farmer satisfaction with this system is high. IoT-based irrigation can be a flexible and sustainable way to improve food security, according to this study, but its deployment calls on sufficient legislative backing, education, and digital infrastructure. These results offer recommendations for more study in diverse agro-climatic settings as well as a scientific foundation for the advancement of precision agriculture.